Pre-Trained Multilingual Sequence-to-Sequence Models: A Hope for Low-Resource Language Translation? - Lee, En-Shiun Annie; Thillainathan, Sarubi; Nayak, Shravan; Ranathunga, Surangika; Adelani, David Ifeoluwa; Su, Ruisi; McCarthy, Arya D. (2022)
Abstract to come...